2021
DOI: 10.1136/bmjopen-2020-045441
|View full text |Cite
|
Sign up to set email alerts
|

Economics of healthcare access in low-income and middle-income countries: a protocol for a scoping review of the economic impacts of seeking healthcare on slum-dwellers compared with other city residents

Abstract: IntroductionPeople living in slums face several challenges to access healthcare. Scarce and low-quality public health facilities are common problems in these communities. Costs and prevalence of catastrophic health expenditures (CHE) have also been reported as high in studies conducted in slums in developing countries and those suffering from chronic conditions and the poorest households seem to be more vulnerable to financial hardship. The COVID-19 pandemic may be aggravating the economic impact on the extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This big difference revealed that LMICs were unprepared to handle a crisis of overwhelming magnitude such as that of the SARS-CoV-2 pandemic [ 6 ]. The combination of insufficient vaccine numbers, scarcity of hospitals and ICU resources, poverty, and social distress became the perfect recipe for chaos, which further debilitated the healthcare infrastructure of LMICs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This big difference revealed that LMICs were unprepared to handle a crisis of overwhelming magnitude such as that of the SARS-CoV-2 pandemic [ 6 ]. The combination of insufficient vaccine numbers, scarcity of hospitals and ICU resources, poverty, and social distress became the perfect recipe for chaos, which further debilitated the healthcare infrastructure of LMICs [ 7 ].…”
Section: Introductionmentioning
confidence: 99%